B12 Characterising gene expression changes in mouse lines with varying repeat lengths in HTT. (13th September 2016) - Stone, Timothy; Elliston, Linda; Brooks, Simon; Holmans, Peter; Dunnett, Stephen B; Jones, Lesley
Abstract : Background: Mouse models are commonly used to study HD. Poly-Q knock-in mice are the most similar in terms of their genomic context and these mice show a late-onset behaviour phenotype. Lin and Detloff have created an allelic series of mice with expanded regions of knock-in CAG repeats. Aims: We would like to know whether the knock-in mice recapitulate any of the gene expression changes that characterise the biology of HD and whether they suggest additional biological pathways worth further investigation. Method: We investigated striatal gene expression changes in mice with 50, 100, 150, 200 and 250 CAG repeats knocked into the Htt locus, at 6, 12 and 18 months of age. We observed gene expression changes in striatal brain tissue that were associated with changes in CAG repeat-length using linear models. We followed this by using standard geneset analysis techniques to determine underlying biological processes that were altered as a consequence of these changes. We extended this analysis to perform Weighted Gene Co-Expression Network Analysis (WGCNA) on the entire dataset to obtain a series of modules of genes with patterns of co-ordinated gene expression across the complete cohort, and to identify key genes (hub genes) that are highly correlated with the module eigengene which can then be statistically tested to see if they associate with repeat-length. These are useful because the associated hub genes could indicate possible therapeutic targets and/or indicate key genes that have been compromised in the progression of the mouse phenotype. Results: Biological processes associated with CAG-length include protein phosphorylation, alternative splicing, synaptic events and learning and memory. WGCNA analysis yields 28 modules of genes of which 14 contain eigengenes that are statistically associated with CAG repeat-length. These modules re-affirm previous findings relating to the biological changes associated with HD, mitochondrial processes, DNA damage, transport and transcriptional regulation but also indicate interesting areas for further study, including extracellular signalling. Conclusions: The gene-expression changes in the allelic series mouse recapitulate several biological processes known to characterise the human form of the disease. The analysis also suggests new areas of biology that could generate additional understanding into the aetiology of this disease.